Adaptabilidade e estabilidade de genótipos de cevada e relações de causa e efeito com o rendimento de grãos - Kobata, Sarha Giovana Kazue (2019)
Climate, genetics and management determine the production and quality of barley grains for brewing purposes, thus, the study of environmental interferences in grain yield based on parameters of adaptability and stability and analysis of correlation and trail between the characters helps in the formulation of selection criteria for promising genotypes and indication of cultivars. The present study aims to evaluate the adaptability and stability of barley genotypes and to verify the cause and effect relationships between characters on grain yield in four environments. The experiment was conducted in a randomized complete block design with three replicates at each site and year. Three methods were used to assess adaptability and stability: Annicchiarico (1992), Eberhart and Russel (1966) and GGE Biplot - mean and instability (YAN, 2001). The cultivar Danielle stood out in relation to the stability and productive average, with wide adaptability. The lines were promising for their adaptability to favorable and / or unfavorable environments, especially Lin03, Lin04 and Lin09 in unfavorable environments and Lin07 in favorable environments. For the analysis of the trail, the explanatory characteristics were: plant height (ALT), hectoliter weight (PH), number of spikes per m2 (NEM), number of grains per spike (NGE), protein content and a thousand grain weight (PMG). A trail analysis was performed for each location and year. The yield components varied in the explanation of the yield of grains, in each place and year, demonstrating that the selection based on the characters under study should be carefully analyzed individually in relation to the place and year, based on a historical average.